Towards Design of High Spin Metal-free Materials - Thanh, Nguyen Van; Tuan, Nguyen Anh (Communications in Physics, 2014)
In this paper, in order to explore high-spin carbon-based magnetic materials with strong ferromagnetic coupling, geometric structure, electronic structure and magnetic properties of alternating stacks of \(π \)-radical-halogenated-hydrocarbons and diamagnetic molecules have been investigated based on density-functional theory with dispersion correction. These alternating stacks are predicted to avoid the typical antiferromagnetic spin-exchange of indentical face-to-face radicals via spin polarization of a diamagnetic molecule in between. Our results show that \(π\)-radical-halogenated-hydrocarbons like perchlorophenalenyl (C\(_{13}\)Cl\(_{9})\) is strong ferromagnetic coupling if alternatingly stacked with aromatics like fluorinated coronene (C\(_{24}\)F\(_{12})\) or coronene (C\(_{24}\)H\(_{12})\), while fluorinated perinaphthenyl (C\(_{13}\)F\(_{9})\) and perinaphthenyl (C\(_{13}\)H\(_{9})\) are not an equally good choice. The role of ligand configuration in determining exchange coupling in stacks is discussed. These results would give some hints for designing new high-spin carbon-based ferromagnetic materials